Angioplasty of a persistent sciatic artery: case report - Denis Szejnfeld (Jornal Vascular Brasileiro, 2011)
Transluminal balloon angioplasty is a good choice for the treatment of lower limb arterial occlusion. Although there are some guidelines addressing its indications, some situations are so unusual that there is no consensus on their management. The presence of a persistent sciatic artery is a rare congenital anomaly of the circulatory system and may be associated with early atheromatous degeneration and occlusion. The authors describe the case of an 81-year-old woman that presented with a history of rest pain, atrophic lesion and no distal pulses. Angiogram depicted a persistent sciatic artery with segmental occlusion and distal disease. The therapeutic option was balloon angioplasty of the occluded segment, with technical and clinical success at mid-term follow-up.